2009
DOI: 10.1108/03090560910923300
|View full text |Cite
|
Sign up to set email alerts
|

Consumer evaluation of unbranded and unlabelled food products

Abstract: PurposeThis study sets out to explore how consumers evaluate unbranded and unlabelled food products and to what extent they are able to select the products with the highest potential to meet their expectations regarding eating quality.Design/methodology/approachThe study focused on Portuguese consumers and their purchase of bacalhau, i.e. salted and dried cod, which is sold unpacked, unbranded and unlabelled in supermarkets. The collection of data encompassed observations of shoppers in supermarkets, individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Consumers evaluate food product quality prior to purchase by product cues, such as retail product packaging (Sogn-Grundvåg & Østli, 2009). Previous studies have suggested that packaging design produces affective reactions (Underwood, 2003) and facilitates consumer quality judgments (Anselmsson et al, 2007;Orth et al, 2010).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Consumers evaluate food product quality prior to purchase by product cues, such as retail product packaging (Sogn-Grundvåg & Østli, 2009). Previous studies have suggested that packaging design produces affective reactions (Underwood, 2003) and facilitates consumer quality judgments (Anselmsson et al, 2007;Orth et al, 2010).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…The relationship between producers and consumers is characterised by an information mismatch that can cause difficulties to consumers who presumably want to understand the real value of a product. Sogn‐Grundvag and Østli () study how consumers evaluate unbranded and unlabelled food products and explore their ability to select the products with the highest potential to meet their expectations regarding eating quality. Results indicate that Portuguese consumers, in spite of substantial experience in buying, preparing and consuming bacalhau , are uncertain in their in‐store quality assessment and often use rather curious quality criteria: touching the dried and salted cod trying to ‘feel’ the quality was common, some even broke the fish tail to assess the dryness.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Even though packaging is important in presenting products, many products are provided without packaging, labeling, or branding. To compensate for the absence of packaging, users usually tend to physically inspect the products to add to their expectations and perceptions . Currently, unpacked products can be arranged into specific shapes to attract users.…”
Section: At the Point Of Purchasementioning
confidence: 99%
“…Sogn-Grundvåg and Østli, 68 Olsson and Györei, 69 Valenzuela and Raghubir 70 Products' presentation on shelves affect users' perception.…”
Section: Orientation Of Design Elementsmentioning
confidence: 99%
See 1 more Smart Citation